2021
DOI: 10.1128/msphere.00154-21
|View full text |Cite
|
Sign up to set email alerts
|

Genome Investigation of Urinary Gardnerella Strains and Their Relationship to Isolates of the Vaginal Microbiota

Abstract: Gardnerella is a frequent member of the urogenital microbiota. Given the association between Gardnerella vaginalis and bacterial vaginosis (BV), significant efforts have been focused on characterizing this species in the vaginal microbiota. However, Gardnerella also is a frequent member of the urinary microbiota. In an effort to characterize the bacterial species of the urinary microbiota, we present here 10 genomes of urinary Gardnerella isolates from women with and without lower urinary tract symptoms. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…It should also be noted that while 16S rRNA gene sequencing is able to confidently distinguish species with divergent sequences, some members of the urogenital microbiota, namely Gardnerella spp., possess highly similar 16S rRNA sequences and their speciation requires further genetic information. 81 …”
Section: Discussionmentioning
confidence: 99%
“…It should also be noted that while 16S rRNA gene sequencing is able to confidently distinguish species with divergent sequences, some members of the urogenital microbiota, namely Gardnerella spp., possess highly similar 16S rRNA sequences and their speciation requires further genetic information. 81 …”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the inconsistency in associations with lower urinary tract symptoms reflects that different Gardnerella species have greater or less capacity to influence the bladder. It has been noted that G. piotii has not yet been isolated from urine, while most other species and subspecies of Gardnerella have been isolated from both niches ( Putonti et al., 2021 ). However, this could be attributed to differences in the culture techniques that were used in studies isolating Gardnerella from the urine compared to those that isolated Gardnerella from the vagina.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the Gardnerella test strain JCP8151B used in the majority of described experiments is now considered to be G. piotii () [27–29, 52]. Urinary isolates (four species of Gram-positive cocci, four species of Gram-negative bacilli, and one yeast species) were obtained from patients with urinary tract infections seen at the Texas Tech University Health Sciences Centre Urology Clinic under an IRB approved protocol and deidentified prior to use in this study ().…”
Section: Methodsmentioning
confidence: 99%
“…At the time of acquisition, all Gardnerella strains were identified as G. vaginalis by the repositor; however, the published emended descriptions [29] and resolution of species [27] have indicated that our strains include three G. vaginalis, three G. piotii, one G. leopoldii, and one Gardnerella gsp12 (Table 1). In fact, the Gardnerella test strain JCP8151B used in the majority of described experiments is now considered to be G. piotii (Table 1) [27][28][29]52]. Urinary isolates (four species of Gram-positive cocci, four species of Gram-negative bacilli, and one yeast species) were obtained from patients with urinary tract infections seen at the Texas Tech University Health Sciences Centre Urology Clinic under an IRB approved protocol and deidentified prior to use in this study (Table 1).…”
Section: Bacterial Strains Media and Growth Conditionsmentioning
confidence: 99%